Answer:
1) Attached
2) 150-3p = 3p-30
3) P=30, Q=60
4) 150-3p = 3p-90
5) P=40 and Q=30
6) Ps=Pd+10
7) P=35, Q=45
8) P=45, Q=45
Step-by-step explanation:
We can write the equation for the quantity demanded as:
And the equation for the quantity supplied as:
1) Attached
2) The equilibrium price can be calculated by making the quantity supplied equal to quantity demanded:
3) The equilibrium price is P=30.
The equilibrium quantity can be calculated as:
The equilibrium quantity is Q=60.
4) The supply now becomes:
The equation for the new equilibrium price is:
5) The new equilibrium is at p=40 and Q=30
6) They will receive
7) In this case, the quantity supplied becomes:
The new price equilibrium becomes P=35:
The quantity for this equilibrium is Q=45:
8) Now, the equations for demand and supply are:
The equilibrium price and quantity becomes: